Implementation of Multicultural Education in Education Practice at Indonesia - Miftahul Huda; Tahir Nubatonis; Uus Ruswandi (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2021)
Indonesia has a population of more than 240 million people with hundreds of ethnic groups and all their substances, has the potential for inter-ethnic conflict, if each ethnic group does not have an attitude of tolerance between one another. To address this, the role of education in providing an understanding of tolerance is very much needed. This study aims to describe the implementation of multicultural education in educational practice. The method used in this study uses a qualitative approach to the literature study method. The results of the research are that multicultural education is a means of understanding the importance of tolerance through the design of cultural competencies in the form of: 1) individual competence to respect, 2) cultural competence and 3) cultural competence development by concocting 4 factors involved in the learning process, which are related to factors : 1) the character of the students, 2) the nature of the teacher, 3) the pedagogy and 4) the content of the curriculum.